Next-generation genome-scale models for metabolic engineering. (December 2015) - King, Zachary A; Lloyd, Colton J; Feist, Adam M; Palsson, Bernhard O
Graphical abstract: Highlights: COBRA methods have become widely used tools in metabolic engineering. Predictions of COBRA methods have led to experimental strain improvements. Next-generation models incorporate new biological networks and simulation types. These models will lead to many new types for predictions for metabolic engineering. Abstract : Constraint-based reconstruction and analysis (COBRA) methods have become widely used tools for metabolic engineering in both academic and industrial laboratories. By employing a genome-scale in silico representation of the metabolic network of a host organism, COBRA methods can be used to predict optimal genetic modifications that improve the rate and yield of chemical production. A new generation of COBRA models and methods is now being developed — encompassing many biological processes and simulation strategies — and next-generation models enable new types of predictions. Here, three key examples of applying COBRA methods to strain optimization are presented and discussed. Then, an outlook is provided on the next generation of COBRA models and the new types of predictions they will enable for systems metabolic engineering.